Teacher Strategies in Character Education Development in Kindergarten - Kurniasaih, Eva Rizki; Suliyem, Suliyem; Wulandari, Suci (Indonesian Journal of Early Childhood Education Studies, 2014)
Character education is an attempt to create the next generation who have superior character. This expaectations will not be achived easily without the theacher’s role as an educator especilly early childhood educator in character building. The purpose of this study is : 1) to understanding the stratrgy in the development character education used by teachers in TK-1 and TK-2, 2) to understanding the learning management including planning, implementation and evaluation of character education in TK-1 and TK-2, 3) to understanding supporting and pursue factors of character education in TK-1 and TK-2. This study used the comparative method of qualitative research. Data collection techniques used observation, interview and documentation. The result of this study shows the strategy in TK-1 is teacher’s modeling, routinely or habituation. While the strategy in TK-2 used integrated with learning, habituation and giving rewards. Planning in TK-1 consist of making an integrated curriculum with character education, integration with daily activities, the evaluation is done by observation technique. While the planning in TK-2 making a specific curriculum, the implementation is done with daily activities, the character education assessment contained in the column of akhlaqul karimah. The supporting factors of character education in TK-1 and TK-2 is the teacher’s competence, learning media and infrastructure. The pursuers factor in TK-1 and TK-2 is the parents do not instill character education at home.How to citeKurniasaih, E., Suliyem, S., & Wulandari, S. (2014). Teacher Strategies in Character Education Development in Kindergarten. Indonesian Journal Of Early Childhood Education Studies, 3(2), 94-101. doi:10.15294/ijeces.v3i2.9481